Cakupan Pelayanan Vaksinasi Covid-19 Dosis Ke-3 Pada Lansia Di Puskesmas Karangdoro Semarang Timur - Koten, Siprianus Hide; Ratih Kumala Dewi (Jurnal Rekam Medis & Manajemen Infomasi Kesehatan, 2023)
It is known that the national vaccination coverage for dose 1 is 93.56%, dose 2 is 74.63%, and dose 3 is 29.24%. From this data it is known that the implementation of booster vaccines is still very low, especially in the elderly which is only 33% or around 7,196,711 elderly people who have just received booster vaccination. This study aims to determine the coverage of the 3rd dose of Covid-19 vaccination for the elderly at the Karangdoro Community Health Center, East Semarang. This research is a quantitative study with a cross sectional approach. The population is 3,425 elderly people aged 60 years and over who live in the Karangdoro Community Health Center. The sample in this study used the Slovin formula with probability sampling technique. The sample size obtained in this study was 150 elderly respondents. The results of the research are that there is no significant relationship between the variable history of comorbid diseases and the utilization of the 3rd dose of Covid-19 vaccination services for the elderly at the Karangdoro Community Health Center with a p-value = 0.579 and there is a significant relationship on the knowledge variable with a p-value = 0.579. 0.003, a perception variable with a p-value = 0.001 regarding the utilization of the 3rd dose of Covid-19 vaccination services for the elderly at the Karangdoro Community Health Center, East Semarang. The government is advised to increase the education and confidence of the elderly regarding the 3rd dose of Covid-19 vaccination by providing information about the 3rd dose of the Covid-19 vaccine that is easily accessible in the environment.